The house of pain and the insect politician: Surveillance and the body in The Fly and The Island of Dr. Moreau. (1st November 2019) - Riede, Austin
AbstractDavid Cronenberg's The Fly (1986), the definitive film of the body horror genre, poses political questions regarding the limits of human recognition and the disciplinary surveillance techniques employed over the body by ideology. This article reads The Fly alongside H. G. Wells's 1896 novel The Island of Dr. Moreau, arguing that both texts are allegorical explorations of the foundation of human politics, through surveillance and control of both individuals and populations. Brundle's transformation leads him to a Hobbesian 'state of nature', in which he asserts his natural right of self-preservation. The vivisected animals that Dr Moreau creates, however, exist in a highly ritualized political system predicated on the human capacity to experience, understand and remember pain. It is a political system that exemplifies Foucauldean notions of self-control through disciplinarian surveillance. The two texts serve as inverted reflections of one another: in The Island of Dr. Moreau, animals are humanized by the fear of pain, and in The Fly a human is animalized by the experience of pain. Both texts are reminders that, as Elaine Scarry has pointed out, pain has the capacity to eradicate individual humanity. They also remind us that empathy for the pain of others is essentially humanizing.